GameSkills : a fun approach to learning sport skills - Hanrahan, Stephanie J., 1961-; Carlson, Teresa B., 1955- (Champaign, IL : Human Kinetics, 2000)
Describes over one hundred games and activities designed to help develop fitness, general movement, and sport-specific skills in people age eight and older; each with an age range, statement of benefits, instructions, equipment needs, safety considerations, and variations.
Choice
Professional
Professional
Keywords: Physical education and training -- Curricula; Physical education